Memory and synaptic plasticity are impaired by dysregulated hippocampal O-GlcNAcylation - Yang, Yong Ryoul; Song, Seungju; Hwang, Hongik; Jung, Hoon Jung; Kim, Su-Jeong; Yoon, Sora; Hur, Jin-Hoe; Park, Jae-Il; Lee, Cheol; Nam, Dougu; Seo, Young-Kyo; Kim, Joung-Hun; et al. (NATURE PUBLISHING GROUP, 2017)
O-GlcNAcylated proteins are abundant in the brain and are associated with neuronal functions and neurodegenerative diseases. Although several studies have reported the effects of aberrant regulation of O-GlcNAcylation on brain function, the roles of O-GlcNAcylation in synaptic function remain unclear. To understand the effect of aberrant O-GlcNAcylation on the brain, we used Oga(+/-)mice which have an increased level of O-GlcNAcylation, and found that Oga(+/-)mice exhibited impaired spatial learning and memory. Consistent with this result, Oga(+/-)mice showed a defect in hippocampal synaptic plasticity. Oga heterozygosity causes impairment of both long-term potentiation and long-term depression due to dysregulation of AMPA receptor phosphorylation. These results demonstrate a role for hyper-OGlcNAcylation in learning and memory.
Keywords: LINKED N-ACETYLGLUCOSAMINE; RECEPTOR GLUR1 SUBUNIT; GLCNAC MODIFICATION; MASS-SPECTROMETRY; AMPA RECEPTOR; PHOSPHORYLATION SITES; OXIDATIVE STRESS; AGING BRAIN; SYNAPSIN I; PROTEIN